CH Bond Activation by Metal–Superoxo Species: What Drives High Reactivity?1. Issue 2 (21st November 2014) - Ansari, Azaj; Jayapal, Prabha; Rajaraman, Gopalan
Abstract Metal–superoxo species are ubiquitous in metalloenzymes and bioinorganic chemistry and are known for their high reactivity and their ability to activate inert CH bonds. The comparative oxidative abilities of M–O2.− species (M=CrIII, MnIII, FeIII, and CuII) towards CH bond activation reaction are presented. These superoxo species generated by oxygen activation are found to be aggressive oxidants compared to their high‐valent metal–oxo counterparts generated by O⋅⋅⋅O bond cleavage. Our calculations illustrate the superior oxidative abilities of FeIII– and MnIII–superoxo species compared to the others and suggest that the reactivity may be correlated to the magnetic exchange parameter.